Efektivitas Terapi Kelompok Pada Pasien Isolasi Sosial Di Wilayah Kerja Puskesmas Limboto Kabupaten Gorontalo - Lahay, Merianti (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Social isolation is the experience of being alone from someone and feeling aversion to others as something negative or threatening and failure to relate to others. The aim of this research is to identify social isolation before providing group therapy to social isolation patients in the working area of ​​the Limboto Community Health Center, Gorontalo Regency. Methods: The method used in this research is a pre-experiment one group pre-test post-test design. Results: It is known that the mean value of the pre test is 13.20 and the post test is 17.00, the standard deviation of the pre test is 000 and the post test is 422, the standard error of the pre test is 1.033 and the post test is 3.682, and the total data is 10 for the pre test and post, as well as the Sig value. 2-tailed is 0.002 <0.05, meaning that there is an influence on effectiveness before and after group therapy is carried out on social isolation patients in the Limboto Community Health Center working area. Conclusion: The patient's condition before being given the socialization group therapy intervention showed that the patient still liked to be alone, shy, and did not want to interact with other people. After being given the socialization group therapy intervention, the patient experienced changes such as being willing to communicate with other people, while the other patients were still unable to communicate with the nurse but with those closest to you there has been a change.